Difficulties and errors in the management tactics of patients with chronic pancreatitis - I V Maev; Iu A Kucheriavyĭ; A A Samsonov; D N Andreev (Терапевтический архив, 2013)
The paper deals with the difficulties and errors that are most commonly used in clinical practice to manage patients with chronic pancreatitis (CP). The higher interest in CP is inspired by the wide prevalence of this disease with its constant upward trend. At the same time, a variety of the etiological forms of CP, from generically determined to infectious and autoimmune ones, in combination with a weak theoretical basis in a number of practitioners gives rise to a broad spectrum of tactical errors in the management of patients with CP. The paper summarizes and analyzes the most common defects and errors in the management tactics of patients with this nosological entity, including the aspects of diagnosis and medical treatment. Ways to solve the set optimization problems in management protocols for patients with CP are proposed in the context of evidence-based medicine.